2023
DOI: 10.7759/cureus.36663
|View full text |Cite
|
Sign up to set email alerts
|

Novel Per-Oral Cricopharyngotomy for Cricopharyngeal Bar: Feasibility Study With Emphasis on Technical Limitations

Abstract: Per-oral endoscopic cricopharyngotomy (c-POEM) is a treatment for cricopharyngeal dysfunction, specifically cricopharyngeal bars (CPB). C-POEM differs from other endoscopic surgical procedures, such as per-oral endoscopic myotomy (POEM), gastric per-oral endoscopic myotomy (g-POEM), and Zenker per-oral endoscopic myotomy (z-POEM). We report three patients who underwent c-POEM for CPB, their clinical course, and outcomes. We underwent a single institution retrospective chart review of three patients who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Therefore, although balloon dilatation is a reasonable alternative, successive dilatations could lead to submucosal fibrosis, making the subsequent myotomy, if required, more difficult. We recognize concerns about C-POEM recently raised by Pittala et al [ 13 ], who reported 3 cases that all developed an esophageal leak post-endoscopy. They determined that this was due to difficulty working within the hypopharynx and conducting the initial mucosotomy, alongside other technical aspects.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, although balloon dilatation is a reasonable alternative, successive dilatations could lead to submucosal fibrosis, making the subsequent myotomy, if required, more difficult. We recognize concerns about C-POEM recently raised by Pittala et al [ 13 ], who reported 3 cases that all developed an esophageal leak post-endoscopy. They determined that this was due to difficulty working within the hypopharynx and conducting the initial mucosotomy, alongside other technical aspects.…”
Section: Discussionmentioning
confidence: 85%
“…We would agree that the most challenging aspect of the procedure is the mucosotomy, which sets the precedent for a successful procedure. It is interesting to see that Pittala et al [ 13 ] started their mucosotomy 2 cm above the bar, whereas we would argue that the mucosotomy should take place directly over the bar to ensure orientation and enable tunnelling down into the esophagus, rather than inadvertently into the pharynx. Use of a conical transparent distal attachment can help within the tight space of the hypopharynx.…”
Section: Discussionmentioning
confidence: 94%
“…Peroral endoscopic myotomy (POEM) is a well-established third-space endoscopic technique that can be technically challenging when used to treat a cricopharyngeal bar, even for experienced operators, due to the limited working space in the hypopharynx and upper esophageal sphincter 1 2 . Here we propose the use of saline immersion to improve the technical success rate of the procedure.…”
Section: Figmentioning
confidence: 99%
“…It is an endoscopic technique for treating cricopharyngeal bar [166,167] or oropharyngeal dysphagia associated with Parkinson's disease [168]. The procedure involves a submucosal injection and a mucosal incision performed approximately 2 cm above the cricopharyngeal muscle.…”
Section: Cricopharyngeal Peroral Endoscopic Myotomy (C-poem)mentioning
confidence: 99%